Lateglacial and early Holocene evolution of the Tyne Valley in response to climatic shifts and possible paraglacial landscape legacies - Yorke, L; Chiverrell, RC; Schwenninger, J-L (Elsevier, 2023)
This paper presents new sedimentological, geomorphological, and optically stimulated luminescence (OSL) geochronological evidence for fluvial evolution of the mid- to lower River Tyne through the Lateglacial to late Holocene. These data reveal a series of fluvial terraces produced by cycles of aggradation and incision, conditioned by glacial inheritance and driven by changing sediment availability and hydrological regime. The distribution and stratigraphy (where available) of nine river terrace and their associated sediments have been recorded. At two key sites the sediments have been dated using OSL measurements to constrain the fluvial geomorphology. Significant entrenchment of the fluvial system, followed by aggradation formed the earliest fluvial terrace (T1), which encompasses environments spanning the transition from deglaciation into Greenland Interstadial 1 (GI-1). Incision below T1 began towards the end of GI-1, with three terraces (T2 – T4) between the abandonment of T1 and the early Holocene (15.0–9.2 ka). Climatic shifts, limited vegetation cover/soil development, and peri−/paraglacial landscape instability conditioned the development of the early postglacial fluvial landsystem. Three further terraces (T5 – T7) developed during the mid- to Late Holocene (6.6–3.1 ka), and comprise most of the valley floor. Climatic instability, glacial inheritance, and widespread anthropogenic disturbances are reflected in greater hillslope-channel coupling during this period. The extent of later Holocene terraces (T8 – T9) is limited as the river became isolated from flanking hillslopes entrenched between existing river terraces. Fluvial landscape evolution in formerly glaciated catchments is strongly conditioned by the cold stage legacy that introduced excess sediment and landscape instability into the catchment. Subsequent catchment-wide responses are variable and non-linear, with valley floors operating in a series of reach-wide responses. There is a need for greater chronological control to constrain the Lateglacial and Holocene evolution in the Tyne catchment, but also to further our understanding of region-wide responses to external drivers and local dynamics.